Net best-ball team composition in golf - Wu, Y.; Chow-Whiteand, P.; Swartz, T. B. (Journal of Sports Analytics, 2019)
This paper proposes simple methods of forming two-player and four-player golf teams for the purposes of net best-ball tournaments in stroke play format. The proposals are based on the recognition that variability is an important consideration in team composition; highly variable players contribute greatly in a best-ball setting. A theoretical rationale is provided for the proposed team formations. In addition, simulation studies are carried out which compare the proposals against other common methods of team formation. In these studies, the proposed team compositions lead to competitions that are more fair.